PEMIMPIN PEREMPUAN YANG BALINESE DALAM PERSPEKTIF HINDU - TARY PUSPA, IDA AYU (Jurnal Studi Jender SRIKANDI, 2007)
Woman in Hinduism positioned really glorify. Wowan of non becoming subordinate men but parallel to run duty wife. Cultural effect of patriarchi growing on society cause the motion step the woman of few blocked. Custom meetings seldom entangle the woman although she is a men in marriying to enter. With the existence of progress and equivalence gender hence woman own the opportunity to work in public sector not merely in domestic sector. During there is opportunity, hence opportunity which sure unfolding can be reached for by the inclusive of becoming leader. With the nature of which feminism woman can lead expressively but must also measure up to do to taking decision. To be come the leader, woman can refer Bahagawadgita, Asta Brata, Niti sastra and holy book of other Hindu.